Improved Topologies Of Series Resonant And Llc Resonant Dc-Dc Converters For Medium Output Voltage Applications - Samsudin, Nor Azura (2017)
Resonant converters are currently the preferable choice of power conversion for many low and medium voltage applications. Double series resonant dc-dc converter has lesser component count, good efficiency and better voltage gain compared to other series resonant dc-dc converters operating in discontinuous conduction mode. However, it has the issue of non-uniform voltage stress on transformers. Similarly, LLC resonant dc-dc converters have been extensively explored for low output voltage applications; however, their benefits in the medium voltage power supply application are not well explored. This thesis proposes four improved topologies of resonant medium voltage dc-dc converters to address the aforementioned issues. First of all, a double series resonant dc-dc converter having uniform voltage stress on transformers is proposed. The secondary windings of the both transformers are connected in series and fed to a voltage multiplier circuit, therefore, the proposed converter solves the problem of non-uniform voltage stress on transformers without any compromise in the performance. Next, a double series resonant dc-dc converter with single transformer is proposed. In this converter, transformer has two primary windings and one secondary winding. Due to the use of single transformer, the converter has smaller size, lower core losses and consequently better efficiency. The third and fourth proposed topologies are full-bridge LLC resonant inverter fed voltage multiplier based medium voltage dc-dc converters. In order to make the realization of LLC operation easier, the turn ratio of transformers is reduced by using voltage multiplier circuits at the secondary sides in both converters. Using a voltage multiplier circuit, the turn ratio of transformer is reduced and LLC operation of converter can be easily achieved. The third proposed converter has only one resonant tank. While, the fourth proposed converter has two resonant tanks. Due to the use of two resonant tanks, the load current is equally divided between two resonant tanks, so that it has lower current stress on the components of the resonant tanks. The main features of these LLC resonant dc-dc converters are good control with narrow variation in switching frequency and lower switching and conduction losses. The performance and effectiveness of all the proposed converters is verified by both the simulation and experiment. In all the proposed converters, power switches and output diodes operate under soft-switching conditions; therefore, the proposed converters have lower switching loss and higher efficiency. Among all the proposed converters, interleaved LLC resonant inverter fed voltage multiplier based medium voltage dc-dc converter is the best choice, because it has the highest efficiency about 95 % at 300 W output power compared to other three proposed converter topologies.